Inisiasi Kemandirian Siswa MTs Nurul Islam Sekarbela Melalui Praktikum Kelistrikan dan Kemagnetan Untuk Mendukung Program Merdeka Belajar - Dian W. Kurniawidi; Rohani Sayuti; Muh. Alfaris; Agus Wahid H; Susi Rahayu (Universitas Mataram, 2023)
The learning process requires media to attract students' attention and curiosity about the lesson. The era of digitalization of technology and information has caused students to start leaving books behind, creating an egocentric attitude focused on themselves. Experiment activities in the laboratory are indicated to be able to initiate collaboration and communication skills, in addition to fostering student independence in learning. This program aims to improve students' competency in literacy and numeracy so that they are better prepared and more relevant to the times. The activity lasts for 3 days, the first and second days are for experiments, while the third day is discussion and evaluation. Experiment materials are electricity and magnetism as much as 5 topics. Based on the completed questionnaire, students understood the Seeback Effect and Magnetic Field Identification up to 96%, while the most difficult topics to understand was Generators and Transformers with an understanding percentage of 76% and Parallel Series Circuits by 88%.